Cortical Potentials Evoked by Deep Brain Stimulation in the Subthalamic Area - Devergnas, Annaelle; Wichmann, Thomas (Frontiers in Systems Neuroscience, 2011)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) has been used since the mid-1990s as a treatment for patients with Parkinson’s disease, and more recently also in other conditions, such as dystonia or obsessive compulsive disorder. Non-invasive studies of cortical evoked potentials (EPs) that follow individual STN-DBS stimuli has provided us with insights about the conduction of the DBS pulses to the cortex. Such EPs have multiple components of different latencies, making it possible to distinguish short-latency and long-latency responses (3-8ms and 18-25ms latency, respectively). The available evidence indicates that these short- and long-latency EPs correspond to STN-cortical conduction via anti- and orthodromic pathways, respectively. In this review we survey the literature from recording studies in human patients treated with STN-DBS for Parkinson’s disease and other conditions, as well as recent animal studies (including our own) that have begun to elucidate details of the pathways, frequency dependencies and other features of EPs. In addition, we comment on the possible clinical utility of this knowledge.